THE AWARENESS AND REALIZATION OF GRICEâS COOPERATIVE PRINCIPLES IN THE CONVERSATIONS AMONG NON-NATIVE ENGLISH SPEAKERS - -, Retnowaty (English Education Journal, 2013)
Pragmatics gives different interpretation of meaning even when it is not said or written. This study was using descriptive qualitative approach. The objects of the study were non-native English speakers at the fourth semester of post-graduate program (S2) majoring English Education of Semarang State University in the academic year 2012/2013. The unit of analysis of this study were utterances which contain the observance and non-observance of Griceâs cooperative principle. Furthermore, to know how they were aware of those principles, a pragmatic awareness test was given to each participant. Based on the test, most participants were aware enough of Griceâs cooperative principle. From all utterances, most participants appeared to observe the maxim of relation. It can be inferred that they tried to answer the question with relevant answer. The realization of non-observance of Griceâs cooperative principle was mostly shown in flouting the maxim of quantity that they gave more or less information than it was needed. Moreover, we can infer that non-native English speakers who were aware of Griceâs cooperative principle would be easier to realize it in their conversations because they understood the concept of how to create successful, effective and efficient communication.